Encapsulation of a drug into electrospun fibers spun from water soluble polymers to control solubility and release - Lan Yi; Lemeng Shi; János Móczó; Béla Pukánszky (Heliyon)
Electrospun fibers prepared from water-soluble polymers (PVP, PVA, and HPMC) were loaded with pregabalin, a BCS I drug, to address its fast release and adverse effects. The drug dissolved partially (1.8–2.8 wt%) in the polymers, with excess pregabalin in crystalline form within the fibers. The solubility of the drug varied with the pH of the dissolution medium. Most of the drug encapsulated into the fibers during electrospinning, but some was lost due to technical reasons. PVP showed no impact on drug release, offering no benefit as a carrier. However, PVA-based fibers exhibited considerably slower release than the dissolution rate of the neat drug and also the release rate from fibers prepared from the other polymers. This indicates the potential of PVA for using it with pregabalin in practical drug formulations with improved release properties. The pH of the dissolution medium influenced solubility and release rate for specific polymers. Overall, the study highlights the importance of polymer selection and pH control in optimizing the release profile of pregabalin in enhanced drug delivery.